ANALISIS DEFORESTASI MENGGUNAKAN REGRESI LOGISTIK MODEL DI TAHURA SEKITAR TANJUNG PROVINSI JAMBI - Indri Febriani; Lilik Budi Prasetyo; Arya Hadi Dharmawan (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2017)
Deforestation cause damage to the environment, climate change and greenhouse gas emissions. Deforestation in Tahura was caused by ilegall logging and forest fire. To reduce deforestation and greenhouse gas emissions, Tahura can participate in REDD+ scheme. REDD+ scheme is a scheme to reduce emissions from deforestation and forest degradation and provide incentives if it is able to reduce emissions. Related to REDD+ was required information on forest cover change (deforestation) and predictions. The method that used in the deforestation analysis, namely logistic regression. This study shows that forest cover in Tahura has changed from 2000 to 2015. Changes in forest cover into a bush is the biggest change with a percentage of 71%. Factors which is tested in logistic regression method i.e. the distance from the road, the distance from the river, the distance from the plantation and total population. Based on the prediction of deforestation, forest area that deforested amount of 103 ha in 2030.